Odontochilus nandae (Orchidaceae; Cranichideae; Goodyerinae), a new species from Nepal - Raskoti, Bhakta Bahadur; Kurzweil, Hubert (Phytotaxa, 2015)
Odontochilus Blume (1859: 79) comprises about 40 species distributed from the Himalayas and China through Southeast Asia eastwards to the southwestern Pacific islands (Chen et al. 2009, Pearce & Cribb 2002, Pridgeon et al. 2003). Most species are restricted to tropical and warm-temperate regions. The genus is closely related with Anoectochilus Blume (1825: 411) and most of species were in the past included in that genus because both genera have flowers with pectinate or dentate (rarely smooth) lip flanges. However, Odontochilus is separated from Anoectochilus based on the saccate non-exerted spur that is largely enclosed by the bases of the lateral sepals, whereas Anoectochilus has an exerted conical or cylindrical spur (Pridgeon et al. 2003).